Spiritual Approach to Improve Anti-Bullying Based Learning at MTs NU Nurul Huda Kudus - Astutik, Ulya Wiji; Nurdianzah, Erry (Universitas Wahid Hasyim Semarang, 2024)
The recent rise in bullying cases that have hit various educational institutions at all levels has caused profound problems. More than that, Indonesia is currently ranked 5th in the world in cases of bullying in educational institutions. This research aims to examine spiritual approaches in learning to improve anti-bullying based learning. This research is qualitative field research with a case study approach. Data collection was carried out by interviewing school principals, teachers and students, observing the implementation of anti-bullying-based education with a spiritual approach and documenting school documents, like; lesson plans, report and school collaboration documents. Data analysis was carried out by sorting, grouping, coding and then looking for appropriate themes for interpretation. The research results show that a spiritual learning approach can be carried out by strengthening learning materials and integrating learning materials. Reinforcing learning has a greater impact compared to integrating learning. The importance of learning with a spiritual approach to the development of students is the internalization of noble religious teachings. So that it can form good behavior and keep students away from bullying behavior that currently still often occurs among Indonesian students.